Child Trauma Exposure and Posttraumatic Stress Disorder: Identification in Community Mental Health Clinics. Issue 2 (2nd July 2016) - Chemtob, Claude M.; Gudiño, Omar G.; Luthra, Rohini; Yehuda, Rachel; Schmeidler, James; Auslander, Brian; Hirshbein, Hillel; Schoor, Alan; Greenberg, Rick; Newcorn, Jeffrey; Panzer, Paula G.; Schenk, Todd; et al.
ABSTRACT: We examined the identification of trauma exposure and posttraumatic stress disorder (PTSD) in help-seeking urban children ( N = 157) presenting for care in community mental health clinics. Children and their parents completed a standard intake assessment conducted by a community clinician followed by a structured, trauma-focused assessment conducted by a study clinician. Clinicians provided ratings of child functional impairment, parents reported on internalizing/externalizing problems, and children provided self-reports of PTSD symptom severity. Although community clinicians were mandated by clinic policy to ask about exposure to physical abuse, sexual abuse, and witnessed domestic violence, they identified exposure to these at significantly lower rates than study clinicians. Rates of PTSD based on community clinician diagnosis (1.9%) were also much lower than rates obtained by study clinicians (19.1%). A review of clinical charts 1 year after intake revealed no change in PTSD diagnosis rate following additional clinical contacts. Clinician-rated impairment, parent-rated emotional/behavioral problems, and child-rated PTSD symptom severity measures provided support for the validity of trauma exposure and PTSD as identified by study clinicians. Trauma exposure and PTSD diagnosis among help-seeking urban youth appear to be underidentified by community clinicians, which may compromise clinicians' ability to respond to environmental risks and provide appropriate evidence-based treatments.